Bibliometria e scienze del libro: internazionalizzazione e vitalità degli studi italiani - Simona Turbanti (Studi e saggi, 2017)
The vitality of a scientific field is usually attested by the fallout that research and publications have on the community of scholars who practice it and, therefore, on the development of the discipline itself and of its methodologies. The degree of "health" of a field of study, as well as its ability to get out of its niche of scholars and to see its validity recognised, is assessed by analysing whether and to what extent the works are read, commented on, cited by scholars from other geographical contexts and / or other scientific branches. The volume presents a research focused on the analysis of the level of internationalisation and vitality of Italian studies in the disciplines related to the study of books and documents, conducted through a series of parallel bibliometric investigations (query of citation databases, searches in Google scholar, application alternative metrics, library catalog analysis).